Learning to be a scientist: viva education: science works for kids series - Moore, Jo Ellen (Viva Education New Delhi, 2004)
This engaging book introduces children to the basics of scientific inquiry and exploration. Through hands-on experiments and observations, it encourages kids to ask questions, make hypotheses, and discover the world around them, fostering a love for science and discovery.